Evaluation of coenzyme Q10 administration in attenuating oxidative responses of β-Amyloid aggregation in models of Alzheimer's disease: A systematic literature review (Research, Society and Development, 2021)
The aim of this study was to evaluate the effects of CoQ10 administration on attenuation of oxidative responses by β-Amyloid aggregation in models of Alzheimer's disease. The present work is a systematic review of the literature, consisting of steps established by search strategies, identification, selection and eligibility of studies. CoQ10 or ubi-quinone and ubidecarenone, is a pro-vitamin synthesized in an endogenous way, this has been used in clinical trials to evaluate its potential for neuroprotection and antioxidation. The findings showed that CoQ10 has antioxidant effects and decreases the intracellular deposition of the beta-amyloid compound, exerting oxidative relief and anti-apoptotic effect. The administration of CoQ10 demonstrated significant results in the attenuation of oxidative responses of β-Amyloid aggregation in AD models.